Eye Tracking as a Tool for Detecting Alzheimer's Disease in People With Down Syndrome. - Piro‐Gambetti, Brianna; Krinsky‐McHale, Sharon; Kovacs, Cynthia; Handen, Benjamin; Christian, Bradley; Laymon, Charles M.; Minhas, Davneet; Luo, Weiquan; Yoon, Dasoo Milton; Fleming, Victoria L.; Schworer, Emily; Kirkorian, Heather; et al. (Journal of Intellectual Disability Research, 2025)
Background: Adults with Down syndrome (DS) experience an increased risk of Alzheimer's disease (AD). Valid cognitive assessments for adults with DS with severe/profound intellectual disability (ID) are needed. It is unclear whether eye tracking is feasible for detecting AD in DS. Method: Fifty‐three adults with DS completed a visual paired comparison (VPC) task, a battery of cognitive measures, and underwent PET scanning. Study partners reported on the participant's dementia symptoms. Bivariate correlations assessed associations between eye‐tracking metrics and AD‐related pathology and symptomatology. Analyses included the full sample (n = 53) and a subgroup with an IQ ≤ 45 (n = 33). Results: Greater fixation duration during the habituation phase was associated with better cognitive performance on the Modified Cued Recall Test (mCRT) (intrusions: r = −0.39, p = 0.011) and less PET tau (r = −0.47, p = 0.014). Larger saccadic amplitudes during the test phase were associated with younger age (r = −0.45, p < 0.001), better cognitive performance on the mCRT (total: r = 0.31, p = 0.041; intrusions: r = −0.33, p = 0.032) and less PET Aβ (r = −0.40, p = 0.025). Greater preference to fixate on the novel image was associated with fewer dementia symptoms (count: r = −0.44, p = 0.002; duration: r = −0.38, p = 0.009). This pattern of significance remained for the subgroup with lower IQ scores. Conclusion: The VPC task is a potentially useful method for assessing AD‐related cognitive impairments in adults with DS across varying ID levels.